Hepatitis C Virus Testing Among Men With Human Immunodeficiency Virus Who Have Sex With Men: Temporal Trends and Racial/Ethnic Disparities. (17th April 2021) - Li, Jun; Armon, Carl; Palella, Frank J; Tedaldi, Ellen; Novak, Richard M; Fuhrer, Jack; Simoncini, Gina; Carlson, Kimberly; Buchacz, Kate; ,
Abstract: Background: National guidelines recommend that sexually active people with human immunodeficiency virus (PWH) who are men who have sex with men (MSM) be tested for hepatitis C virus (HCV) infection at least annually. Hepatitis C virus testing rates vary by race/ethnicity in the general population, but limited data are available for PWH. Methods: We analyzed medical records data from MSM in the HIV Outpatient Study at 9 human immunodeficiency virus (HIV) clinics from January 1, 2011 through December 31, 2019. We excluded observation time after documented past or current HCV infection. We evaluated HCV antibody testing in each calendar year among HCV-seronegative MSM, and we assessed testing correlates by generalized estimating equation analyses. Results: Of 1829 eligible MSM who were PWH, 1174 (64.2%) were non-Hispanic/Latino white (NHW), 402 (22.0%) non-Hispanic black (NHB), 187 (10.2%) Hispanic/Latino, and 66 (3.6%) of other race/ethnicity. Most were ≥40 years old (68.9%), privately insured (64.5%), with CD4 cell count/mm 3 (CD4) ≥350 (77.0%), and with HIV viral load <200 copies/mL (76.9%). During 2011–2019, 1205 (65.9%) had ≥1 HCV antibody test and average annual HCV percentage tested was 30.3% (from 33.8% for NHB to 28.5% for NHW; P < .001). Multivariable factors positively associated ( P < .05) with HCV testing included more recent HIV diagnosis, public insurance, lower CD4, prior chlamydia, gonorrhea, syphilis, or hepatitis B virus diagnoses, and elevated liver enzyme levels, but not race/ethnicity. Conclusions: Although we found no disparities by race/ethnicity in HCV testing, low overall HCV testing rates indicate suboptimal uptake of recommended HCV testing among MSM in HIV care. Abstract : There were no discernable racial/ethnic disparities in HCV testing among MSM within the HOPS during 2011-2019. However, low annual HCV testing rates across all racial and ethnic groups indicated suboptimal uptake of recommended HCV screening.